Critical risk identification in construction projects using 2D and 3D risk matrices - Shamal Ali Othman; Dalshad Kakasor Ismael Jaff; Ahmet Öztaş (PLoS ONE, 2026)
Construction projects are exposed to numerous risks that may adversely affect project cost and duration. The purpose of this study is to identify and prioritize key construction risks by combining a Work Breakdown Structure (WBS) with a Risk Breakdown Structure (RBS) and analyzing these risks using two-dimensional (2D) and three-dimensional (3D) risk matrices. In total, 63 risk factors were identified and categorized into five main areas of the work breakdown structure: earthwork, concrete, finishing, mechanical, and electrical. The questionnaire was designed based on each risk category and then sent to engineers, who were asked to estimate the risk probability and its impact. In total, 378 engineers responded. The respondents data were analyzed by using the risk matrix method. Two separate 3D risk matrices were made: one was based on multiplying all three data points, and the other was based on combining both impacts. The results clearly show that the 3D matrix, which combines cost and time impact, yields more accurate results than the matrix that multiplies cost impact and time impact.